DESAIN BALANCE SCORECARD DI KOPERASI SYARIAH SEKAR TANJUNG KECAMATAN ARJASA KABUPATEN JEMBER - Oktaviansyah, Hendrik Tri; Rachman, Riza (Relawan Jurnal Indonesia, 2022)
Performance measurement is very important, because performance measurement can later be used as a performance evaluation in the future by taking into account financial and non-financial aspects. The purpose of this study was to determine the BSC design in Koperasi Syariah Sekar Tanjung. This research is a qualitative research, that data in the form of descriptive explanations that explain a description of certain objects and results. This study uses the BSC perspective to design the BSC in Koperasi Syariah Sekar Tanjung Jember. The data analysis method used is describing the vision and mission, SWOT analysis, determining alternative strategies, causal relationships between perspectives, determining lead and lag indicators of alternative strategies as well as targets and initiatives of strategic objectives, and determining implementation mechanisms. Koperasi Syariah Sekar Tanjung Strategy, Arjasa District, Jember Regency, when designed using BSC seen from 4 perspectives, it is necessary to improve the quality of human resources, improve the quality of excellent service to customers, increase customer satisfaction, and increase financial ratios.